A Teacher’s Deconstruction of Disability: A Discourse Analysis - Kang, Jong-Gu (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Batang; panose-1:2 3 6 0 0 1 1 1 1 1; mso-font-alt:¹ÙÅÁ; mso-font-charset:129; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:fixed; mso-font-signature:1 151388160 16 0 524288 0;} @font-face {font-family:"\@Batang"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:129; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:fixed; mso-font-signature:1 151388160 16 0 524288 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; text-align:justify; mso-pagination:none; text-autospace:none; word-break:break-all; font-size:10.0pt; mso-bidi-font-size:12.0pt; font-family:Batang; mso-hansi-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-font-kerning:1.0pt; mso-fareast-language:KO;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->In this study I use critical discourse analysis to explore how one special education teacher who is informed by a sociocultural perspective of disability deconstructs disability in the way that she talks about her practice as a special educator and about her work with students who are labeled as having disabilities. By analyzing her discourse, I reveal the positioning of the teacher in relation to her school and show the importance that language plays in constructing and deconstructing disability, knowledge, and power.